Ethical health security in the age of antimicrobial resistance. Issue 1 (7th January 2022) - Pahlman, Kari; Fehross, Anson; Fox, Greg J; Silva, Diego S
Abstract : Objective: Owing to its potential human, social and economic costs, antimicrobial resistance (AMR) is frequently referred to as a threat to health security. Simultaneously, health security and the preservation of antimicrobials are often described as a global public good. However, how the term 'public good' is used in the context of health security, and the values that underpin it, remains ambiguous. Policymaking is never value-free, and a better examination of such values is critical to understanding how issues such as AMR are problematised and how policy decisions are informed. Design: We used McDougall's version of critical interpretive synthesis to capture the recurring concepts and arguments within public policy, political science and applied ethics literature on AMR. Articles were analysed by identifying recurring ideas and developing themes across the literature. Results: A total of 77 papers were included in our review. In the context of health security and AMR, the concept of 'public good' appears to be used interchangeably with 'common good', reflecting confusion, but sometimes meaningful differences, regarding how antimicrobials, as a good, are conceived. Main approaches to addressing AMR are statism, globalism and regionalism, which appeal to different values in guiding policymakers. Common justificatory values underpinning preservation of antimicrobials as a public good were prevention of harm, solidarity, justice and rights. Conclusion: The findings suggest that within the literature there is a lack of conceptual clarity as to whether antimicrobials constitute a public good or a common good. Moreover, the way in which antimicrobials are conceived and the approaches through which AMR as a threat to health security is addressed appear to be grounded in values that are often implicit. Being explicit about the values that underpin AMR and health security is not simply an intellectual exercise but has very real policy and programmatic implications.